2014
DOI: 10.1111/jmft.12073
|View full text |Cite
|
Sign up to set email alerts
|

Stress From Daily Hassles in Couples: Its Effects on Intradyadic Stress, Relationship Satisfaction, and Physical and Psychological Well‐Being

Abstract: According to the systemic-transactional stress model (STM; G. Bodenmann, European Review of Applied Psychology, 1997; 47: 137), extradyadic stress from daily hassles can have a negative impact on the individual psychological and physical health and the couple's relationship. This study is the first one to test the STM propositions in a model that includes both partners' individual and relational outcomes simultaneously. The model also includes actor and partner effects as well as the interdependence between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
141
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(190 citation statements)
references
References 63 publications
23
141
3
6
Order By: Relevance
“…We also found that negative perception of SLEs experienced during the past year was associated with lower levels DoS, and lower DoS was linked with poorer psychological health outcomes. Research has shown that major stressful events have a negative impact on health (e.g., Falconier et al., ; Rosengren et al., ), and our results suggest that one of the pathways is through deficits in DoS (e.g., greater levels of emotional cutoff and heightened emotional reactivity).…”
Section: Discussionsupporting
confidence: 64%
“…We also found that negative perception of SLEs experienced during the past year was associated with lower levels DoS, and lower DoS was linked with poorer psychological health outcomes. Research has shown that major stressful events have a negative impact on health (e.g., Falconier et al., ; Rosengren et al., ), and our results suggest that one of the pathways is through deficits in DoS (e.g., greater levels of emotional cutoff and heightened emotional reactivity).…”
Section: Discussionsupporting
confidence: 64%
“…During periods of relatively high external stress, couples are more likely to indicate they are struggling with such relational issues as having less time to connect with one another, a lack of intimacy within the marriage, feeling neglected by their partner, and increased differences in attitudes with the partner [21, 22]. In essence, stressful contexts impose additional challenges on the couple, by constraining the types of experiences couples accrue within the relationship, which ultimately can erode marital happiness.…”
Section: Route 1: Stressful Contexts Create Additional Problems Withimentioning
confidence: 99%
“…The links between daily extradyadic stress and both individual (e.g., psychological symptoms; Bodenmann et al, ; Falconier et al, ) and relationship (e.g., sexual problems and relationship quality or satisfaction; Bodenmann et al, , ) outcomes are often mediated by daily intradyadic stress. However, extradyadic stress was more predictive of own sexual functioning for both genders and had more influence on sexual functioning than psychological symptoms or relationship quality; further, for women, intradyadic stress was more predictive of sexual problems, whereas for men extradyadic stress was more predictive of sexual problems (Bodenmann et al, ).…”
Section: Review Of Research On Dyadic Daily Stressmentioning
confidence: 99%
“…Negative work-family spillover has consequences for individual well-being and has been a popular area of study (e.g., Grzywacz, 2000;Grzywacz & Marks, 2000). Daily workand family-related stress tend to co-occur (Grzywacz, Almeida, & McDonald, 2002), and attempts to examine daily extra-and intradyadic stress and relationship outcomes, (e.g., closeness, sexual satisfaction) confirm the notion of spillover of extradyadic to intradyadic stress (Bodenmann, Ledermann, & Bradbury, 2007;Falconier, Nussbeck, Bodenmann, Schneider, & Bradbury, 2015;Ledermann, Bodenmann, Rudaz, & Bradbury, 2010). Moreover, many findings suggest that the accumulation of intradyadic stress (resulting from stressors such as conflict or negative interactions) explains how extradyadic stress has an impact on relationship outcomes.…”
Section: Conceptualizing Stress In Intimate Relationshipsmentioning
confidence: 99%